2011
DOI: 10.1371/journal.pone.0023121
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Spectrally Distinct Rhodopsins in Aedes aegypti R7 Photoreceptors

Abstract: The retina of the mosquito Aedes aegypti can be divided into four regions based on the non-overlapping expression of a UV sensitive Aaop8 rhodopsin and a long wavelength sensitive Aaop2 type rhodopsin in the R7 photoreceptors. We show here that another rhodopsin, Aaop9, is expressed in all R7 photoreceptors and a subset of R8 photoreceptors. In the dorsal region, Aaop9 is expressed in both the cell body and rhabdomere of R7 and R8 cells. In other retinal regions Aaop9 is expressed only in R7 cells, being local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Sison-Mangus et al, 2006;Awata et al, 2010), Diptera (e.g. Hu et al, 2011) and the two-spotted cricket (Henze et al, 2012), a dorsal-ventral gradient or regionalization was found with higher expression of longwavelength opsins in ventral eye regions.…”
Section: Research Articlementioning
confidence: 90%
See 2 more Smart Citations
“…Sison-Mangus et al, 2006;Awata et al, 2010), Diptera (e.g. Hu et al, 2011) and the two-spotted cricket (Henze et al, 2012), a dorsal-ventral gradient or regionalization was found with higher expression of longwavelength opsins in ventral eye regions.…”
Section: Research Articlementioning
confidence: 90%
“…Whereas in most cases two opsins of similar absorption spectra are co-expressed, combinations of UV and blue opsins have been reported in the mosquito Aedes and the butterfly Parnassius (Awata et al, 2010;Hu et al, 2011). The co-expression of blue and green opsins in five out of eight photoreceptors per ommatidium (which results in broad spectral sensitivity curves) may be an adaptation to low light conditions.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…However, the Aaop7 transgenic fly retains high sensitivity to shorter wavelengths (400 and 350 nm) and does not exhibit the second peak response in the UV observed for Drosophila Rh1 (Fig. 4C,D) and Aaop2, the only other long-wavelength Aedes opsin that has been analyzed in this way (Hu et al, 2011).…”
Section: The Spectral Properties Of Aaop7 Rhodopsinmentioning
confidence: 93%
“…Three of these groups are labeled as long-wavelength (>500 nm), short-wavelength (400-500 nm), and UV-sensitive rhodopsin (<400 nm), and two of these groups contain uncharacterized family members. We previously characterized the patterns of rhodopsin expression in the adult Aedes compound eye (Hu et al, 2009(Hu et al, , 2011(Hu et al, , 2012(Hu et al, , 2014. These studies revealed features of the visual system in Aedes that were not predicted from study of other invertebrate models.…”
Section: Introductionmentioning
confidence: 99%